Determinación Del Costo De Producción Del Yogur Casero En La Microempresa Orlandia “Un Mundo De Lácteos”, Mediante La Metodología De Costo Por Procesos (2020)
In the present work, the study of costs generated in the production of the yogurt, that is why the following title is proposed for the object of study: Determination of the Production cost of yogurt in the Orlandia microenterprise "A world of dairy products" in Neiva (Huila), through the process cost methodology; microenterprise dedicated to the production and marketing of dairy products.